Analisis Yuridis Terhadap Efektivitas Kebiri Kimia Sebagai Hukuman Bagi Pelaku Kejahatan Seksual Anak Di Indonesia - Dinda Prema Santoso; Arista Chandra Irawati; Hetiyasari Hetiyasari (Qistie Jurnal Ilmu Hukum, 2025)
Sexual crimes against children are a serious issue that requires effective legal handling. One of the punishments implemented in Indonesia is chemical castration. This study aims to analyze the effectiveness of chemical castration as a punishment for perpetrators of child sexual abuse in Indonesia from a juridical perspective. This study aims to analyze the effectiveness of chemical castration as a punishment for perpetrators of child sexual abuse in Indonesia from a juridical perspective. The research utilizes a normative and empirical juridical approach, with data collection techniques involving document studies and secondary literature. Theories employed in this study include the Law Enforcement Theory, Criminal Justice System Theory, and Due Process Theory. Despite chemical castration being regulated under Law Number 17 of 2016 on Child Protection and Government Regulation Number 70 of 2020, its implementation faces various obstacles. The findings reveal significant legal gaps and challenges in the execution of chemical castration, including the lack of detailed regulations and procedural clarity. Recommendations are provided to improve the effectiveness of chemical castration, such as revising regulations, enhancing coordination among relevant institutions, and ensuring adequate training and certification for medical practitioners involved in the procedure.